1992
DOI: 10.1021/jm00080a018
|View full text |Cite
|
Sign up to set email alerts
|

New neplanocin analogs. 1. Synthesis of 6'-modified neplanocin A derivatives as broad-spectrum antiviral agents

Abstract: Novel neplanocin A analogues modified at the 6'-position, i.e., 6'-deoxy analogues (2, 3, 6, 9, 20), 6'-O-methylneplanocin A (15), and 6'-C-methylneplanocin A's (22a and 22b) have been synthesized and evaluated for their antiviral activity in a wide variety of DNA and RNA virus systems. These compounds showed an activity spectrum that conforms to that of S-adenosylhomocysteine hydrolase inhibitors. They were particularly active against pox- (vaccinia), paramyxo-(parainfluenza, measles, respiratory syncytial), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(19 citation statements)
references
References 4 publications
0
19
0
Order By: Relevance
“…The sources of the three compounds used in this study were TJ13025, Toyo Jozo Research Center, Ohito, Shizuoka, Japan (16).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sources of the three compounds used in this study were TJ13025, Toyo Jozo Research Center, Ohito, Shizuoka, Japan (16).…”
Section: Methodsmentioning
confidence: 99%
“…Inhalation of aerosolized ribavirin by infants with RSV pneumonia or college students with influenza A leads to an improvement of the clinical symptoms in these patients (7,19,20). The mechanism of action of ribavirin and its metabolism by cells have been investigated (5,6,17,18,21); the main targets for the antiviral action of ribavirin and its phosphorylated form appear to be IMP dehydrogenase, viral mRNA cap formation, and viral RNA transcriptase or polymerase.Recently, we have reported two novel nucleoside analogs, 5 -ethynyl -1-, -D -ribofuranosylimidazole -4 -carboxamide (EICAR) and 6'-(R)-6'-C-methylneplanocin A (TJ13025), as broad-spectrum antiviral agents active against a wide variety of pox-, toga-, reo-, myxo-, rhabdo-, and arenaviruses in vitro (3,16). In this study, we have evaluated the inhibitory effects of EICAR and TJ13025 in comparison with those of ribavirin on the in vitro replication of several ortho-and paramyxoviruses.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to VV, the moderate activities of compounds 14 and 15 against this virus are similar to that of IIIc (like 14 and 15 a 6-amino-8-azapurine derivative), which shows that an extra methyl group on the carbon bearing the hydroxyl of these compounds does not greatly alter their anti-VV activity, which remains of a magnitude similar to that of ribavirin and well below that of brivudin. With regard to RSV, the marked activity of the 6-aminopurine IIIb (about 15-fold less than those of neplanocin A and 6Ј-C-methylneplanocin A, 14) but of the same magnitude as that of ribavirin and more than 130-fold more active than brivudin) is retained by the type V analogue 9 but not by the type VI analogue 10. Curiously, anti-RSV activity of the same magnitude as that of IIIb is displayed by the type VI hypoxanthine derivative 8, whereas the corresponding type V analogue 7 is inactive.…”
mentioning
confidence: 98%
“…13) In addition, it has been reported that a 6Ј-C-methylneplanocin A (IVa) is more potent and/or selective than neplanocin A (IVb) against cytomegalovirus, vaccinia virus, parainfluenza virus, measles virus, respiratory syncytial virus, Junin virus, Tacaribe virus, vesicular stomatitis virus and reovirus. 14) This fact suggested to us to extend our research to compounds in which the cyclobutane ring bears a 1-hydroxyethyl group instead of the hydroxymethyl group of compounds III.…”
mentioning
confidence: 98%